Acceptability and storage stability of fish loaf from underutilized fish species - Dequilla , Marie Prudence D. (2001.)
Acceptability of fish loaf from different underutilized fish species in Iloilo was investigated.
Thesis - B.S. (Food Technology) - SOTECH, University of the Philippines in the Visayas.
Keywords: Fish loaf